Penerapan Kaidah Tafsir Isim dan Fi‘il dalam QS al-Rum/30: 27: Analisis Kaidah Kebahasaan Khalid bin Sabt - Jannah, Miftahul; Basri, Halimah; Hamzah, Amir (Dirosah Islamiyah, 2026)
Differences in the interpretation of Qur'anic verses are closely related to the application of Arabic linguistic principles that serve as the foundation for contextual textual understanding. This study aims to analyze the application of the interpretive principles of ism (noun) and fi‘l (verb) in Qur'an 30:27 based on the linguistic framework proposed by Khalid bin al-Sabt and to examine its implications for interpretive differences. This research employs a qualitative descriptive approach using library research. Primary data consist of Qur'an 30:27 and Khalid bin al-Sabt's principles concerning ism and fi‘l, while secondary data are derived from classical and contemporary Qur'anic commentaries as well as relevant scholarly literature. Data were analyzed using content analysis through the stages of identifying linguistic forms, examining the application of interpretive principles, comparing exegetical perspectives, and analyzing their semantic implications. The findings reveal that the jumlah ismiyyah structure and the use of the fi‘l muḍāri‘ convey the meanings of continuity and permanence of Allah's power. Furthermore, the term ahwanu gives rise to differing interpretations due to different applications of the ism tafḍīl principle. The study concludes that the descriptive interpretation is more appropriate than the comparative interpretation within the context of the verse, thereby providing a more coherent understanding of Allah's absolute perfection and omnipotence.